Sweden's New Resettlement Policy: Introducing Gender and Gender Equality as Governing Tools in Migration Governance - Suter, Brigitte (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2026)
In 2022, Sweden introduced new refugee selection guidelines prioritizing women and girls—a departure from earlier practices focused solely on vulnerability. Through a problem representation analysis, this article examines parliamentary motions on resettlement from 2015 to 2022, exploring how gender, im/mobility, religion, and vulnerability shape notions of deservingness. It argues that gender is—intentionally or not—used as a governance tool, reflecting a broader migration policy shift of not only framing men and asylum seekers as a problem but creating the grounds for weakening rights-based approaches in favour of a more humanitarian approach to migration governance driven by compassion but also control.